Authors’ Reply to “Neuro-Ophthalmologic Complications of SARS-Cov-2 Infections and Vaccinations” [J Ophthalmic Vis Res 2024;19:140–141] - Mehdi Tavakoli; Danielle R. Isen; Mohadeseh Feizi (Journal of Ophthalmic and Vision Research, 2026)
This letter responds to the letter titled “Neuro-Ophthalmologic Complications of SARS-Cov-2 Infections and Vaccinations,” published in J Ophthalmic Vis Res 2024;19:140–141 with DOI: https://doi.org/10.18502/jovr.v19i1.15451